Length of hospital stay and its factor associated among neonates with perinatal asphyxia in the Northwest Amhara Region, Northwest Ethiopia 2023: a multicentre retrospective cross-sectional study - Gezahagn Demsu Gedefaw; Asnake Tadesse Abate; Degalem Tilahun Worku; Mulugeta Endalamaw Ayenew; Dawit Tesfaye Daka (BMJ Open)
Objective To determine the length of hospital stay and related factors in newborns with perinatal asphyxia in comprehensive specialised hospitals in Northwest Ethiopia.Design A multicentre institutional-based cross-sectional study.Setting Tertiary hospitals in Northwest Amhara Regional State, Northwest Ethiopia, from 1 to 30 December 2023.Participants A total of 609 neonates with perinatal asphyxia were admitted to the neonatal intensive care unit of selected public hospitals in Northwest Amhara from September 2018 to October 2023.Outcome measures Length of hospital stay and associated factors in newborns with perinatal asphyxia were noted.Results A total of 609 newborns with perinatal asphyxia were included in this study. The mean hospital stay for the newborns was 13.9 days (coef=13.9, 95% CI 13.43 to 14.38), with minimum and maximum hospital stays of 4–28 days, respectively. Neonatal sepsis, AKI, hypoxic ischaemic encephalopathy, fetal macrosomia and prolonged labour were significantly associated with a longer hospital stay in neonates with perinatal asphyxia.Conclusions The current study indicated that the mean length of hospital stay in newborns with perinatal asphyxia was 13.9 days. Contributing factors to prolonged hospital stays include neonates with neonatal sepsis, prolonged second-stage labour, acute neonatal kidney injury stages 2 and 3 hypoxic ischaemic encephalopathy and fetal macrosomia. The length of hospital stay for neonates with perinatal asphyxia can be reduced by implementing appropriate standards of care.